ANALISIS TANTANGAN SERTA DIMENSI ETIKA DALAM EKOSISTEM PENDIDIKAN DIGITAL - Iswanto; Mochamad Nurul Amin; Andi Warisno; Nila Wati Tajuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital education has become an essential component of educational transformation in the technological era. The integration of digital technologies offers opportunities to enhance access, flexibility, and the quality of learning. However, its implementation continues to face various challenges, including unequal access to technology, limited digital literacy, data security concerns, and the potential misuse of technology. In addition, ethical issues have emerged as a significant concern, encompassing privacy protection, academic integrity, intellectual property rights, and equitable access for all learners. This study aims to analyze the challenges and ethical dimensions within the digital education ecosystem through a literature review approach by examining relevant academic publications and research findings. The results indicate that the success of digital education depends not only on technological infrastructure but also on the strengthening of digital literacy, supportive policies, and the application of ethical principles. Therefore, collaboration among stakeholders is necessary to create a safe, inclusive, and sustainable digital education ecosystem.